Results of Emergency Appendectomy for Appendicular Mass - Khan, AW; Sheikh, SH; Rahman, MA (Mymensingh Medical Journal, 2007)
Mymensingh Med J. 2007 Jul;16(2): 209-213The abstract of this article is available on the PubMed website